Effectiveness of regdanvimab treatment for SARS-CoV-2 delta variant, which exhibited decreased in vitro activity: a nationwide real-world multicenter cohort study - Kim, Haein; Jang, Young Rock; Lee, Ji Yeon; Ko, Jae-Hoon; Lee, Jee Young; Cho, Seongcheol; Lee, Yong Dae; Song, Junghoon; Hyun, Miri; Kim, Hyun Ah; Hwang, Soyoon; Ryou, Sangmi; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Immune-evading severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants are emerging continuously. The clinical effectiveness of monoclonal antibody agents that exhibit decreased in vitro activity against SARS-CoV-2 variants needs to be elucidated. Methods A nationwide, multicenter, retrospective cohort study was designed to evaluate the effectiveness of regdanvimab, an anti-SARS-CoV-2 monoclonal antibody agent. Regdanvimab was prescribed in South Korea before and after the emergence of the delta variant, against which the in vitro activity of regdanvimab was decreased but present. Mild to moderate coronavirus 2019 (COVID-19) patients with risk factors for disease progression who were admitted within seven days of symptom onset were screened in four designated hospitals between December 2020 and September 2021. The primary outcomes, O2 requirements and progression to severe disease within 21 days of admission, were compared between the regdanvimab and supportive care groups, with a subgroup analysis of delta variant–confirmed patients. Results A total of 2,214 mild to moderate COVID-19 patients were included, of whom 1,095 (49.5%) received regdanvimab treatment. In the analysis of the total cohort, significantly fewer patients in the regdanvimab group than the supportive care group required O2 support (18.4% vs. 27.1%, P < 0.001) and progressed to severe disease (4.0% vs. 8.0%, P < 0.001). In the multivariable analysis, regdanvimab was significantly associated with a decreased risk for O2 support (HR 0.677, 95% CI 0.561–0.816) and progression to severe disease (HR 0.489, 95% CI 0.337–0.709). Among the 939 delta-confirmed patients, O2 support (21.5% vs. 23.5%, P = 0.526) and progression to severe disease (4.2% vs. 7.3%, P = 0.055) did not differ significantly between the regdanvimab and supportive care groups. In the multivariable analyses, regdanvimab treatment was not significantly associated with a decreased risk for O2 support (HR 0.963, 95% CI 0.697–1.329) or progression to severe disease (HR 0.665, 95% CI 0.349–1.268) in delta-confirmed group. Conclusions Regdanvimab treatment effectively reduced progression to severe disease in the overall study population, but did not show significant effectiveness in the delta-confirmed patients. The effectiveness of dose increment of monoclonal antibody agents should be evaluated for variant strains exhibiting reduced susceptibility.